Effects of two different taper models after strength training on corticospinal excitability and muscle strength - Virtanen, Minttu (2018)
Aim: The aim of this study was to investigate if there are (1) differences between the effects of two taper models on strength performance, (2) changes in corticospinal excitability and inhibition as the effect of 8 week of strength training, and (3) changes in corticospinal excitability and inhibition following two different taper models. Methods: Two groups (n = 6 + 5) of recreationally active men first performed 8-week hypertrophic and maximum strength training period, and after that Group 1 performed two weeks of step taper and Group 2 two weeks of linear taper. Squat 1 RM, leg press MVIC, knee extension MVIC and the measurements of corticospinal excitability with transcranial magnetic stimulation were performed six time during the study: week before strength training (conrtol), before strength training, after 5 and 8 weeks of strength training and after one and two weeks of taper. Results: Squat 1 RM improved for both groups through the study whereas MVIC in leg press and knee extension did not change as clearly. There were not statistical differences between groups in any strength results. MEParea with different stimulation intensities, MEPsum and the slope of the I/O-curve remained constant or slightly decreased during the 8-week of strength training period, whereas during the first week of taper they slightly increased for group 1 and slightly decreased for group 2, and during the second week of taper vice versa. AMT and the duration of silent periods did not change significantly during the study. Discussion & conclusion: The results of this study suggest that there are not differences between the effects of step taper and linear taper on strength performance. During the 8-week hypertrophic and maximum strength training period corticospinal excitability remained con-stant or slightly decreased. During taper step taper corticospinal excitability first slightly increased and then slightly decreased whereas during linear taper appeared to happen vice versa.